Youthnation : building remarkable brands in a youth-driven culture - Britton, Matt, 1975- (John Wiley & Sons, 2015)
Youth is no longer an age? It's a commodity. 'YouthNation' is an indispensable brand roadmap to the youth-driven economy. Exploring the idea that youth is no longer an age, it's a commodity that's available to everyone. This book shows what it takes to stay connected, agile, authentic, and relevant in today's marketplace. Readers will learn the ins and outs of the new consumer, and the tools, methods, and techniques that ensure brand survival in the age of perpetual youth. Coverage includes marketing in a post-demographic world, crafting the story of the brand, building engaged communities, creating experiences that inspire loyalty and evangelism, and the cutting-edge tricks that help businesses large and small harness the enormous power of youth. The old marketing models are over, and the status quo is dead. Businesses today have to embody the ideals of youth culture in order to succeed, by tapping the new and rapidly evolving resources in business and in life. When everything is changing at the pace of a teenager's attention span, how do businesses future-fit for long-term success? This book provides a plan, and the thoughts, strategies, and brass tacks advice for putting it into action. Use New-Gen psychographics to target markets. Build stronger evangelism with a compelling brand narrative. Create loyal communities with immersive and engaging experiences. Navigate the radically-changed landscape of the future marketplace. In today's hyper-socialized, Facebook fanatic, selfie-obsessed world, youth is the primary driver of business and culture. Smart companies are looking to tap into the fountain of youth, and the others are sinking fast. 'YouthNation' is a roadmap to brand relevancy in the new economy, giving businesses turn-by-turn direction to their market destination.